GAMBARAN PERILAKU HIDUP BERSIH DAN SEHAT PADA TATANAN RUMAH TANGGA DI RW 04 KELURAHAN TERBAN WILAYAH KERJA PUSKESMAS GONDOKUSUMAN II YOGYAKARTA - Wantiyah Wantiyah; Retno Purwandari (Fakultas Kesehatan Masyarakat, Universitas Jember, 2007)
Health status is influenced by four factors, they are: environment, behavior, personal factor, and health services. From the four factors, the more important factors were environment and behavior. RW 04 is a city in Terban Village, and at the side of Code River with crowded population, that can increases the spreading of communicable disease. That will be worse if the people didn’t pay attention to the clean and health behavior. The purpose of this research is to know the clean and health behavior in household structures at RW 04 Terban. The research is a descriptive research with the approach of cross-sectional survey, has been done in RW 04 Terban Village. The subject are families that live in RW 04 Terban Village, and fulfill the criteria which determined, by sampling technique that is cluster proportional random sampling and accidental sampling, there are 95 families. Instruments used were questionnaire and checklist sheets in nominal scale. The data is analyzed by descriptive analysis Aritmatic Mean. The result is that the clean and health behavior on the good category, with the mean value is 78,32%. Almost families at the third classification (green), and they do 7 until 8 indicators from 10 indicators of the clean and health behavior in household structures. The indicators which on the good category are: nutrition, immunization, fresh water, trash, nail, and toilet. AIDS and JPKM are on the sufficient category, and the indicator of smoking has a bad result. There are differences results of each indicator between the research and the report from Terban Village. The research concluded that the clean and health behavior in household structures at RW 04 Terban Village on the good category, with the highest result is nutrition indicator, and the lowest result is smoking indicator. Smoking is the main problem in RW 04 Terban Village. Keywords: Health status, The clean and health behavior in household structures